Predictors of Academic Performance in the ‘Oral Biology and Pathology’ Paper: A Retrospective Quantitative Study - Khareedi, Rohini (Auckland University of Technology, 2015)
Background: The cohort of students enrolled in the Oral Biology and Pathology paper reflects a structural diversity in that it includes students of multiple ethnicities, varied age groups, differing scholastic and life experiences. These divergent identities of students are known to influence academic performance. Academic performance has been a subject of intense research to not only identify at risk students to remediate failure but to also endorse factors that impact academic performance positively. Purpose: The purpose of this retrospective quantitative study was to determine the ability of a set of variables such as: age, gender, ethnicity, level of prior education, place from which prior education was obtained, work experience and academic performance at university as measured by grades obtained in the prerequisite paper to predict academic performance in the Oral Biology and Pathology paper. Method: The research approach employed for this hypothetico-deductive retrospective study was the quantitative methodology. The sample for this study was a purposive sample of all students who had enrolled in the Oral Biology and Pathology paper at the Auckland University of Technology from 2011 to 2014. The desensitized empirical data of 116 students from the University’s data base was subject to descriptive and inferential statistical analysis. Results: The multivariable regression analysis demonstrated that the grades obtained in the prerequisite paper was a statistically significant predictor variable (p<0.001) for the academic performance in the Oral Biology and Pathology paper. Pearson’s correlation coefficient analysis revealed a statistically significant and a strong positive correlation (r=0.641, p<0.001) between the grades in the prerequisite paper and the grades in the Oral Biology and Pathology paper. Conclusion: The conclusions from the results obtained in our study is that age, gender, ethnicity, level of education, place from where previous educational qualifications were obtained and work experience were neither correlated to nor predictive of the academic performance in the Oral Biology and Pathology paper. The grades obtained in the prerequisite paper was the only variable that was emphatically demonstrated to be correlated to and predictive of the academic performance in the Oral Biology and Pathology paper. Though the conclusions drawn cannot be generalized, the inferences drawn have implications for education practice and future research.
Keywords: Predictors; Academic performance